Nonphysical intimate partner violence: emotional abuse and controlling behavior against women - Zavala, Egbert (Kansas State University, 2007)
Though many studies do show that emotional abuse exists within a pattern of other physical violence, few researchers have adopted nonphysical abuse as the crux of their research. The goal of this study is to contribute to the intimate partner violence literature by examining other forms of abuse such as controlling and emotional abuse that are largely neglected in social science research. More specifically, I examine the connection between women’s employment (status compatibility) and their risk of intimate partner abuse. Examining the role of male power and control in intimate relationship increases our understanding of the causes and consequences of male-to-female violence. Data are from the survey of Violence and Threats of Violence Against Women and Men in the United States, 1994-1996. This survey involved telephone interviews with a national probability sample of approximately 8,000 English-speaking women and 8,000 men ages 18 and older residing in households throughout the United States. Only women are analyzed in this study. Respondents were asked about their general fear of violence and ways in which they managed those fears, emotional abuse on the part of their partners, and incidents of actual or threatened violence experienced by all types of offenders. Taping into status compatibility by measuring women's contribution to relationship economic well-being through employment and education, hypotheses are derived from feminist theory suggesting that women in relationships that benefit men's marital power will experience more emotional abuse than women whose status are compatible with their partners. Consistent with prior research, controlling and emotional abuse is associated with low education attainment and poverty. Results reveal that control and emotional abuse is not greatest in relationships in which a male is employed and their female partner is not or in relationships in which a woman is employed and their male partner is not. Contrary to prior research, relationships in which unemployed men are married to women who work were not found to have experienced more emotional abuse than couples in which both partners are employed.
Keywords: Intimate Partenr Violence; Violence Against Women; Emotional Abuse; Control Against Women; Sociology, Criminology and Penology (0627); Sociology, General (0626); Sociology, Individual and Family Studies (0628)